Pengaruh Kualitas Sistem Informasi Dan Kemudahan Akses Terhadap Loyalitas Pengguna Dengan Kepuasan Sebagai Variabel Mediasi Pada Platform Weverse (Studi Pada Komunitas Digital Fans K-Pop) - Miftahul Syalzidah; Muhammad Ridwan Basalamah; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2026)
Abstract Accessibility on Weverse users' continuous commitment, with satisfaction serving as a mediating variable. Using the Theory of Reasoned Action as the conceptual foundation, this study employed a quantitative approach with an explanatory design, involving 105 active Weverse users from the Malang City region, selected through purposive sampling. Data were collected using electronic questionnaires with Likert scales and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0 software. The measurement model evaluation verified that all indicators met the convergent validity criteria, with factor loadings between 0.785 and 0.908, and Average Variance Extracted values above the 0.50 threshold, along with strong internal consistency reliability as indicated by Composite Reliability and Cronbach's Alpha exceeding 0.70. The empirical results show that platform accessibility has a significant impact on user satisfaction (T-statistic = 3.652; P-value = 0.000) and commitment (T-statistic = 3.578; P-value = 0.000). Contrary to the initial hypothesis, system infrastructure quality did not show a significant influence on satisfaction (P-value = 0.077) or loyalty (P-value = 0.449). Furthermore, satisfaction did not mediate the relationship between these predictors and loyalty. The coefficient of determination reveals that the independent variables explain 20.4% of the variance in satisfaction and 23.8% in user loyalty. Overall, these findings emphasize that operational flexibility and user-friendly features of the platform are primary drivers of loyalty in K-Pop fan digital communities, while concerns about data security and system reliability remain significant barriers in building user loyalty. Keywords: Ease Of Access, User Satisfaction, User Loyalty